PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN DENGAN FRAMEWORK CSS BOOTSTRAP DAN WEB DEVELOPMENT LIFE CYCLE - Roberto Kaban; Fajrillah (Department of Science and Technology Ibrahimy University, 2017)
Bootstrap is an open source CSS framework by providing CSS classes that are already integrated with JQuery. The design responsive layout support on bootstrap will create a website that automatically adjusts to the width of the user's browser so that the website created by bootstrap is compatible with all smartphone, tablet, laptop and desktop PC devices. The design of library information system in this research using Web Development Life Cycle (WDLC) method. WDLC is a method that used to design web-based information systems, stages of system design on WDLC ranging from Planning, Analisys, Design and Development, Testing and Implementation and maintenance. This research produces a responsive web-based information system that enables members and librarians for doing book searching, lending and book returning.